2015
DOI: 10.1002/bdrc.21116
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the young microbiome on inflammatory diseases—Lessons from animal studies

Abstract: Chronic inflammatory diseases are on the rise in the Westernized world. This rise has been correlated to a range of environmental factors, such as birth mode, rural versus urban living conditions, and use of antibiotics. Such environmental factors also influence early life gut microbiota (GM) colonization and maturation--and there is growing evidence that the negative effects of these factors on human health are mediated via GM alterations. Colonization of the gut initiates priming of the immune system from bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 121 publications
(116 reference statements)
0
18
0
Order By: Relevance
“…There is a precedent for use of prophylactic or suppressive antibiotics in the primary care literature for the standard management of pregnant women with recurrent cystitis . Such investigation must also consider possible long‐term adverse outcomes such as obesity, immune or inflammatory disorders, or other conditions related to alterations of the gut microbiome among antibiotic‐exposed infants.…”
Section: Discussionmentioning
confidence: 99%
“…There is a precedent for use of prophylactic or suppressive antibiotics in the primary care literature for the standard management of pregnant women with recurrent cystitis . Such investigation must also consider possible long‐term adverse outcomes such as obesity, immune or inflammatory disorders, or other conditions related to alterations of the gut microbiome among antibiotic‐exposed infants.…”
Section: Discussionmentioning
confidence: 99%
“…Early stimuli can critically affect the developing immune system of the baby, and might lead to the development of atopic, chronic inflammatory and allergic diseases later. These effects are well studied in the case of the gut microbiota, but little is known about the exact nature and effect of the cutaneous microbiota on the pathogenesis of such disease …”
Section: Factors Shaping the Composition Of The Skin Microbiotamentioning
confidence: 99%
“…These effects are well studied in the case of the gut microbiota, but little is known about the exact nature and effect of the cutaneous microbiota on the pathogenesis of such disease. 38…”
Section: The Microbiotamentioning
confidence: 99%
“…During the last years, different animal studies have demonstrated that reduced exposure to microbes early in life is associated with an increased risk of later disease [11, 23]. Moreover, antibiotics-induced microbiota dysbiosis in early life leads to increased susceptibility to allergic and metabolic disorders [2426].…”
Section: Introductionmentioning
confidence: 99%